Core/Whole Genome Multilocus Sequence Typing and Core Genome SNP-Based Typing of OXA-48-Producing Klebsiella pneumoniae Clinical Isolates From Spain - Miro, Elisenda; Rossen, John W. A.; Chlebowicz, Monika A.; Harmsen, Dag; Brisse, Sylvain; Passet, Virginie; Navarro, Ferran; Friedrich, Alex W.; García-Cobos, S. (Frontiers in Microbiology, 2020)
Whole-genome sequencing (WGS)-based typing methods have emerged as promising and highly discriminative epidemiological tools. In this study, we combined gene-by-gene allele calling and core genome single nucleotide polymorphism (cgSNP) approaches to investigate the genetic relatedness of a well-characterized collection of OXA-48-producing Klebsiella pneumoniae isolates. We included isolates from the predominant sequence type ST405 (n = 31) OXA-48-producing K. pneumoniae clone and isolates from ST101 (n = 3), ST14 (n = 1), ST17 (n = 1), and ST1233 (n = 1), obtained from eight Catalan hospitals. Core-genome multilocus sequence typing (cgMLST) schemes from Institut Pasteur’s BIGSdb-Kp (634 genes) and SeqSphere+ (2,365 genes), and a SeqSphere+ whole-genome MLST (wgMLST) scheme (4,891 genes) were used. Allele differences or allelic mismatches and the genetic distance, as the proportion of allele differences, were used to interpret the results from a gene-by-gene approach, whereas the number of SNPs was used for the cgSNP analysis. We observed between 0–10 and 0–14 allele differences among the predominant ST405 using cgMLST and wgMLST from SeqSphere+, respectively, and <2 allelic mismatches when using Institut Pasteur’s BIGSdb-Kp cgMLST scheme. For ST101, we observed 14 and 54 allele differences when using cgMLST and wgMLST SeqSphere+, respectively, and 2–5 allelic mismatches for BIGSdb-Kp cgMLST. A low genetic distance (<0.0035, a previously established threshold for epidemiological link) was generally in concordance with a low number of allele differences (<8) when using the SeqSphere+ cgMLST scheme. The cgSNP analysis showed 6–29 SNPs in isolates with identical allelic SeqSphere+ cgMLST profiles and 16–61 cgSNPs among ST405 isolates. Furthermore, comparison of WGS-based typing results with previously obtained MLST and pulsed-field gel electrophoresis (PFGE) data showed some differences, demonstrating the different molecular principles underlying these techniques. In conclusion, the use of the different WGS-based typing methods that were used to elucidate the genetic relatedness of clonal OXA-48-producing K. pneumoniae all led to the same conclusions. Furthermore, threshold parameters in WGS-based typing methods should be applied with caution and should be used in combination with clinical epidemiological data and population and species characteristics.